Operational Performance of A Controlled Landfill in Bantaeng, Indonesia: Leachate Management, Odor Nuisance, and Institutional Constraints - Amansyah, Munawir; Rahmah, Nur; Az-Ziqra, Aura Annisza; Akmal, Nurfaizah; Alfasyari, Arief; Khaqul, Andi (Unihealth Community Research, 2026)
Municipal solid waste management studies increasingly emphasize landfill upgrading and environmental safeguards, yet limited empirical evidence remains on how controlled landfill operations perform under district-level resource constraints and fluctuating waste inflow, creating a gap in operationally grounded evaluations. This study assesses the operational system and environmental management of TPA Batu Terang, the main final disposal facility in Bantaeng Regency, Indonesia, focusing on daily waste inflow dynamics, leachate and landfill gas management, nuisance impacts, social dimensions, and institutional capacity. A qualitative descriptive case study design was applied using field observations and an in-depth semi-structured interview with the Head of the Environmental Agency. Reported waste inflow averaged 27.49 tons/day, periodically increasing to 30–32 tons/day due to routine clean-up programs and increased food and packaging residuals linked to the Free Nutritious Meal (MBG) initiative. The facility implements controlled landfill practices with periodic soil cover, supported by a weighbridge and computerized recording that enables semi-annual reporting and improves accountability. Environmental management is strengthened by a leachate collection system and staged multi-pond treatment (intake–facultative–maturation–biofilter), described as operating within capacity. However, methane utilization remains limited and odor persists as the most salient community concern, typically addressed through reactive covering. Key constraints include aging heavy equipment, limited budgets, human resource needs, and suboptimal source separation. Findings imply that phased improvements prioritizing routine cover discipline, equipment maintenance financing, incremental gas control and monitoring, and upstream waste diversion are essential to reduce impacts and support transition toward an integrated final processing facility (TPAS).